The construction of plant expression vector of S1 gene of avian infectious branchitis virus - WU Jian-xiang; ZHOU Ji-yong; CHENG Li-qin; SHEN Xing-yan; DING Hong-mei (浙江大学学报. 农业与生命科学版)
The S1 gene of avian infectious bronchitis virus (ZJ971 strain) was amplified by polymerase chain reaction with special primers containing XbalI and BamHI. The purified PCR product was digested by the restricted enzyme XbalI and BamHI. The digested and purified S1 gene of infectious bronchitis virus was cloned into plant expression vector pBI121. The result shows that pBI121 with S1 gene was successfully transferred into Agrobacterium tume faciens (Aotumefaciens) with methods of PCR and restricted enzymes.